Patient experience of pregnancy-related venous thrombosis: A phenomenological study. Issue 183 (November 2019) - Gee, Emma; Roberts, Lara; Arya, Roopen; Tsianakas, Vicki
Abstract: This study used a descriptive phenomenological approach to explore the lived experience of women diagnosed with VTE in pregnancy and the perinatal period. The study setting was a London, university affiliated hospital. The sample consisted of nine women with deep vein thrombosis or pulmonary embolism in pregnancy or up to six weeks post-partum, diagnosed in the last two years. Semi-structured interviews were undertaken using an interview guide. Interviews were transcribed and analysed using phenomenological descriptive analysis. Clustered invariant constituents that represented the lived experience of subjects emerged. The study revealed that the experience of pregnancy-related venous thrombosis is an overwhelmingly negative one with the journey through diagnosis and treatment being fraught with challenges, uncertainty and anxiety. Four main themes that contributed to the women's lived experience were identified: 1. Challenges in establishing a diagnosis; 2. Dealing with diagnosis; 3. Coping with treatment; and 4. Fears for the future. This is the first study to explore the experience of pregnancy-related venous thrombosis and offers valuable insight into the phenomenon. There is opportunity for clinicians to enhance the experience of pregnancy-related venous thromboembolism (PRVTE) by improving communication and information given to patients, clarifying diagnostic and treatment pathways and improving awareness of the condition. Highlights: VTE symptoms in pregnant women were often dismissed by clinicians. Women did not receive enough information throughout their VTE journeys. Fear of impact of VTE on future pregnancies and VTE recurrence were common. VTE generally had a negative impact on women in pregnancy and post-partum. Clinicians have scope to improve the experience of pregnancy related VTE for women.